Vegetation classification of the Witsand Nature Reserve, Northern Cape Province, South Africa - Mthombeni, Thulani Fanifani (University of the Free State, 2019)
Witsand Nature Reserve (WNR) is located in the Northern Cape Province of South Africa on the western side of the Langeberg Mountain range in the triangle between the towns Postmasburg, Olifantshoek and Groblershoop. The study covered the entire reserve of 3 500 ha. The name Witsand is the Afrikaans word for “white sand”. WNR is known for its “roaring” white sand which is a great tourist attraction. These white sand dunes are unique and in strong contrast with the surrounding red Kalahari sand dunes. The occurrence of white sand in the study area is due to the shallow water table under the white dunes. Percolating water has bleached the sand over millions of years. Through this process, red iron oxide, which usually coats sand grains, is leached through water, rendering sand grains white. WNR was established in April 1994, with the primary aim of conserving the unique white sand dune ecosystem. Prior to its proclamation, Witsand was utilised as a farm. Previous human impacts included water abstraction, overgrazing and 4x4 trails which have disturbed the dune system. No river systems are present at or near WNR, yet the Witsand area was a reliable source of water for local farmers in the past. When inundated, a few small ephemeral pans provide fresh water for the animals in the region. The area has a climate that varies from extremely cold winter nights to extremely hot summer days. Rainfall is low and typically peaks toward the end of summer. Precipitation events are mostly in the form of thunderstorms. The geology is dominated by rocks of the Kalahari Group and Olifantshoek Super Group. The former being formed through sedimentary accumulation, which took place approximately 65 million years ago, while the formation of the younger Olifantshoek Supergroup is estimated at 48 million years ago. WNR falls within the semi-arid savanna biome of the Kalahari bioregion where the dominating vegetation type is the Olifantshoek Plain Thornveld, (SVk 13) characterised by scattered trees and shrubs and a ground layer dominated by grasses. The study of this reserve’s vegetation is important, because it allows for the mapping of its plant communities, understanding the relationships between the plant species distributions and environmental factors. This vegetation study allow us to understand how animal and plant interactions function and what actions need to be implemented to ensure biodiversity conservation and management A total of 120 sample plots were placed within homogenous vegetation units throughout the reserve in various habitatssuch aspans, rocky outcrops, sand dunes and sandy plains. Vegetation surveys wereconducted using the Braun-Blanquet method. A modified TWINSPAN classification was applied and resulted in the classification of four plant communities, four subcommunities and four variants. These vegetation units (communities, subcommunities and variants) were described and ecologically interpreted. Various management practices are recommended, which should be incorporated into the management plan of the Witsand Nature Reserve.
Dissertation (M.Sc. (Plant Sciences))--University of the Free State, 2019
Keywords: Witsand Nature Reserve; Vegetation classification; Conservation; Sustainable use; Biodiversity; Braun-Blanquet; Environmental management; Management plans